2020
DOI: 10.1186/s12889-020-8184-0
|View full text |Cite
|
Sign up to set email alerts
|

Men’s perspectives on HIV self-testing in sub-Saharan Africa: a systematic review and meta-synthesis

Abstract: Background: Despite the many HIV testing models implemented in Africa, the level of HIV testing uptake remains relatively poor, especially among men. The HIV self-testing (HIVST) model offers an additional approach for encouraging men to get tested. This study aimed to synthesise evidence on men's perspectives regarding HIVST in sub-Saharan Africa (SSA). Methods: The databases searched included PubMed/MEDLINE, American Doctoral Dissertations via EBSCO host; Union Catalogue of Theses and Dissertations; SA ePubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 51 publications
8
71
0
Order By: Relevance
“…This corroborates well with findings from a similar study conducted in South Africa, which demonstrated key stakeholders' confidence in HIVST improving uptake of HTS in underserved population [31]. A recently published systematic review and meta-synthesis on men's perspectives on HIV self-testing in sub-Saharan Africa recommended presented evidence of poor awareness but high acceptability of HIVST among men [32]. While this is the case; stakeholders expressed concerns that need to be addressed before effective implementation and scale-up can be achieved.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This corroborates well with findings from a similar study conducted in South Africa, which demonstrated key stakeholders' confidence in HIVST improving uptake of HTS in underserved population [31]. A recently published systematic review and meta-synthesis on men's perspectives on HIV self-testing in sub-Saharan Africa recommended presented evidence of poor awareness but high acceptability of HIVST among men [32]. While this is the case; stakeholders expressed concerns that need to be addressed before effective implementation and scale-up can be achieved.…”
Section: Discussionsupporting
confidence: 87%
“…Raising public awareness levels emerged as a key strategy to effective implementation and overall success of scale-up efforts in this study. Similar recommendations have been made elsewhere [31,32,36,37]. Key stakeholders in South Africa [31], researchers, academics, journalists, community advocates, policy makers and other key stakeholders in Nigeria [36] and reviews by Hlongwa et al [32], Johnson et al [37] all recommend need the improve public awareness on HIVST.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Existing evidence suggests that by allowing people to test discreetly and conveniently, HIVST may increase uptake of HIV testing among people not reached by other HIV testing services [10]. According to the WHO, HIVST is defined as: "a process whereby someone collects his or her specimen (oral fluid or blood) and then performs an HIV test and interprets the result, often in a private setting, either alone or with someone he or she trusts" [1].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of HIVST reported in the literature, including reaching first-time testers, older men, and very young and vulnerable people, men who sex with men (MSM), commercial sex workers, and transgender [10][11][12][13][14][15]. Also, HIVST has the advantages of convenience, privacy, anonymity, and a short time to get results, confidentiality, and accessibility.…”
Section: Introductionmentioning
confidence: 99%